Effectiveness Evaluation of Shredded Waste Expanded Polystyrene on the Properties of Binder and Asphalt Concrete - Rocksana Akter; Rain Man Raja (Advances in Civil Engineering)
The disposal of massive amounts of waste, particularly nondecaying waste, is now a major issue for both developed and developing countries. One of the most sustainable solutions to this problem is to recycle garbage into valuable items. Expanded polystyrene, which is manufactured in large quantities, is one of these waste materials. This is being used globally as packaging material, construction material, and household appliances. The waste expanded polystyrene (EPS) is necessary due to its biodegradability, and aesthetically, it has a great negative impact on the environment. The goal of this research would be to see how shredded waste EPS affects the characteristics of asphalt and asphalt concrete. For this, four separate serial asphalt concrete samples were made with varying amounts of shredded expanded polystyrene waste (0.25, 0.50, 0.75, and 1% by the weight of the total aggregate) and five different percentages of asphalt (4.0, 4.5, 5.0, 5.5, and 6.0% by the weight of the total aggregate). In this study, 60/70 grade bitumen was used. Modified asphalt concrete properties were examined and compared with those of the standard specimens. The penetration, ductility, softening point, flash point, and fire point of the asphalt will all be affected by the addition of EPS plastic waste. The optimal asphalt content of the conventional specimen was 5.1 percent, and different percentages of EPS with OAC were applied. The mechanical properties of all specimens were studied in terms of Marshall properties after Marshall specimens were created with regard to OAC by adding EPS. It has been discovered that applying a 0.5% addition produces improved results than other methods. Simultaneously, as the EPS percentage increased, the stability value increased by approximately 82.61% compared to the traditional mix.